Cisplatin-resistant HepG2 cell-derived exosomes transfer cisplatin resistance to cisplatin-sensitive cells in HCC - Zuxiong Tang; Jun He; Jiayue Zou; Shufei Yu; Xiaoming Sun; Lei Qin (PeerJ, 2021)
Backgrounds Cancer cell resistance to chemotherapy drugs such as Gemcitabine, Oxaliplatin, Cisplatin, Doxorubicin, and 5-fluorouracil account for the main reason of chemotherapy failure for HCC patients, especially for those with advanced HCC or metastasis patients. This emerging resistance limits the effectiveness and clinical application of these chemotherapy drugs. Previous studies reported that drug-resistant tumor cell-derived exosomes could transfer their resistance property to tumor sensitive cells in some cancer, including lung and gastric cancer. This study sought to explore whether HepG2/DDP cell-derived exosomes transmit cisplatin (DDP) resistance to HepG2 and other HCC sensitive cells, and provide considerable guidance for HCC nursing with Cisplatin DDP clinically. Methods The HepG2 DDP-resistant cell line (HepG2/DDP) was established, and the exosomes from both HepG2/DDP and HepG2 cells were isolated and named ES-2, ES-1, respectively. HepG2 or SMMC-7721 or Huh7 cells were treated with DDP or DDP + ES-2, and HepG2/DDP cells were treated with ES-1. Then, the activation of drug resistance via HepG2/DDP exosomes transfer to HepG2, SMMC-7721 and Huh7 cells were assessed by cell viability assay and ROS formation. Moreover, the relative expression of P-glycoprotein (P-gp) was measured by western blot analysis. Results HepG2/DDP cell-derived exosomes were successfully isolated from cisplatin-resistant HepG2 cells, and named ES-2. Cell viability of HepG2 or SMMC-7721 or Huh7 cells treated with DDP + ES-2 was enhanced compared with that of DDP treatment group. Also, the concentration of ROS generated in cells under DDP or DDP + ES-2 treatment was strongly increased compared with that of control, although the concentration of ROS was clearly smaller in DDP + ES-2 treatment group compared with DDP treatment. At the same time, the expression of P-gp was upregulated on the ES-2 surface. Conclusion The results mentioned above clarified that HepG2/DDP cell-derived exosomes conferred cisplatin resistance to HepG2 and other HCC cell lines, and provided a new significance for improving the effectiveness of DDP in treating HCC.